2010
DOI: 10.1063/1.3471813
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of the negatively-charged nitrogen-silicon-vacancy center in cubic silicon carbide

Abstract: We performed density-functional theory calculations to study the energetic stability and the electronic structures of negatively-charged nitrogen-silicon-vacancy center (N-VSi)− in cubic silicon carbide (3C–SiC). We show that the (N-VSi)− center is energetically preferable in n-type 3C–SiC and possesses a stable A32 ground state and doubly degenerated E3 excited states. The (N-VSi)− centers prefer to couple weakly in an antiferromagnetic way, triggered by superexchange between them. Our work indicates that 3C–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In addition, if Δ E > 0, it suggests that FM spin alignment is more stable. According to the Heisenberg model, the nearest-neighbor magnetic coupling J 0 can be evaluated using the expression: Δ E = 4 J 0 ( R ) S 2 , where S is the net spin of the defect states . It is known that the main source of the magnetic moment for the V Zn defect arises from the two holes in the 2p band at the O sites surrounding the Zn vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, if Δ E > 0, it suggests that FM spin alignment is more stable. According to the Heisenberg model, the nearest-neighbor magnetic coupling J 0 can be evaluated using the expression: Δ E = 4 J 0 ( R ) S 2 , where S is the net spin of the defect states . It is known that the main source of the magnetic moment for the V Zn defect arises from the two holes in the 2p band at the O sites surrounding the Zn vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…Another defect worth mentioning is the NV Si which is supposed equivalent to NV − in diamond . A recent work shows that the NV Si centre is energetically preferable in n‐type 3C‐SiC and possesses a stable 3 A 2 ground state and doubly degenerated 3 E excited states, however it hasn't been experimentally observed. SiC infrared PL associated with some of its intrinsic defects is thus an exciting platform for telecommunication photonic and opto‐electronics devices.…”
Section: Optical Defects In Sicmentioning
confidence: 99%
“…For a recent review see Doherty et al [1]. The question whether the NV center in diamond is unique or whether similar defects could be generated in other materials has been the object of theoretical studies [2][3][4][5][6][7][8]. These studies suggested that it would be highly desirable to engineer defects with comparable spin and optical properties in more technological materials such as SiC, which would also allow scalability.…”
Section: Introductionmentioning
confidence: 99%